Research on the mobile CDN architecture and the resource scheduling method - Su-fen LI; Yun-yong ZHANG; Bing-yi FANG; Lei XU; Wei XIONG; Jun WU (Tongxin xuebao)
Aimed at network architecture of mobile core network,the deployment method of MCDN service nodes was discussed on the basis of virtualized core net resources and proposes a MCDN network architecture based on the core net resource pool.Then,according to collaborative problem of MCDN resources,a MCDN resource scheduling algorithm based on regional resource co-allocation was proposed,establish a mathematical model of goal programming based on multi-factor resource co-allocation was extablished.Finally,a case study is conducted to demonstrate the feasibility and effectiveness of the proposed approach.